Applied Jigsaw Technique in Increasing Narrative Writing Ability - Amrizal Amrizal; Zohri Hamdani (Ahmad Dahlan Journal of English Studies, 2017)
This aimed to know using of jigsaw technique in increasing narrative writing ability students’ grade seven Junior High School  Muhammadiyah Lampung 3 year 2016/2017. This research of population was all students’ Junior High School  Muhammadiyah Lampung 3, it consisted of four classes. It used random sample which consisted of thirty students and grade seven Junior High School Muhammadiyah Lampung 3 Kec. Labuhan Ratu Kedaton. This research was class action research , the data was analyzed to know increasing students’ narrative writing ability, the researchers used technique of collecting documentation, interview and observation . Data analysis was conducted by taking the average score of the pre-test and post- test in cycle 1 and cycle 2. The result of research showed that the average of result on cycle I was 67,40  while cycle II was 78,30 and there was increasing namely 10,63.